PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN LITERASI DIGITAL DAN HASIL BELAJAR IPA SISWA KELAS IV SEKOLAH DASAR - Anjani, Winna; Setiawardani, Wawan; Khoimatun, Khoimatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Discovery Learning Model on the digital literacy skills and science learning outcomes of grade IV elementary school students. This study used an experimental research design with a quasi-experimental design. The respondents were 60 grade IV students at Riyadhul Muta'allimin Elementary School, divided into two groups: the experimental class, which received treatment with the discovery learning model, and the control class, which only used conventional learning. The research instruments used were a learning outcome test and a digital literacy questionnaire. Data were analyzed using a t-test. The results showed that the average digital literacy score of the experimental class reached 69.30, higher than the control class's score of 63.00. The average science learning outcomes of the experimental class also increased to 80.83, while the control class only achieved 68.67. This improvement in learning outcomes is indicated by an N-gain value of 0.67 in the experimental class and 0.47 in the control class. The t-test obtained a significance level of 0.000 < 0.05, indicating a significant difference between the two classes. Therefore, the application of the discovery learning model is effective in improving science learning outcomes for elementary school students.